The effect of finasteride and dutasteride on the growth of WPE1-NA22 prostate cancer xenografts in nude mice - Opoku-Acheampong, Alexander B.; Nelsen, Michelle K.; Unis, Dave; Lindshield, Brian L. (My University, 2012)
Background: 5 alpha-reductase 1 (5alphaR1) and 5alpha-reductase 2 (5alphaR2) convert testosterone into the more potent androgen dihydrotestosterone. 5alphaR2 is the main isoenzyme in normal prostate tissue; however, most prostate tumors have increased 5alphaR1 and decreased 5alphaR2 expression. Previously, finasteride (5alphaR2 inhibitor) treatment begun 3 weeks post-tumor implantation had no effect on Dunning R3327-H rat prostate tumor growth. We believe the tumor compensated for finasteride treatment by increasing tumor 5alphaR1 expression or activity. We hypothesize that finasteride treatment would not significantly alter tumor growth even if begun before tumor implantation, whereas dutasteride (5alphaR1 and 5alphaR2 inhibitor) treatment would decrease tumor growth regardless of whether treatment was initiated before or after tumor implantation. Methodology/Principal Findings: Sixty 8-week-old male nude mice were randomized to Control, Pre- and Post-Finasteride, and Pre- and Post-Dutasteride (83.3 mg drug/kg diet) diet groups. Pre- and post-groups began their treatment diets 1–2 weeks prior to or 3 weeks after subcutaneous injection of 1x10[5th power] WPE1-NA22 human prostate cancer cells, respectively. Tumors were allowed to grow for 22 weeks; tumor areas, body weights, and food intakes were measured weekly. At study’s conclusion, prostate and seminal vesicle weights were significantly decreased in all treatment groups versus the control; dutasteride intake significantly decreased seminal vesicle weights compared to finasteride intake. No differences were measured in final tumor areas or tumor weights between groups, likely due to poor tumor growth. In follow-up studies, proliferation of WPE1-NA22 prostate cancer cells and parent line RWPE-1 prostate epithelial cells were unaltered by treatment with testosterone, dihydrotestosterone, or mibolerone, suggesting that these cell lines are not androgensensitive. Conclusion: The lack of response of WPE1-NA22 prostate cancer cells to androgen treatment may explain the inadequate tumor growth observed. Additional studies are needed to determine whether finasteride and dutasteride are effective in decreasing prostate cancer development/growth.
Keywords: Prostate cancer; Finasteride; Dutasteride; WPE-NA22 prostate cancer cells